ANALYSIS OF MIGRATION PROCESSES ON THE GREAT SILK ROAD - B.J. Eshov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes migration processes on the Great Silk Road in the middle ages, which has an analysis of the migration of Central Asian nations. Also studied historical geographical problems, caravan routes, and trade sales processes related to migration.